Investigating the Expression of c-Myc and BIRC5 in TRAIL and PBOX-15 treated Metastatic Prostate Cancer Cells - Corinne Kai Leng Chew; Hannah O'Toole; Daniela M Zisterer; Seema M. Nathwani; Jade K. Pollock (SURE Journal: (Science Undergraduate Research Experience Journal))
Purpose Metastatic prostate cancer is associated with poor survival rate and limited treatment options. Overexpression of c-Myc and BIRC5 has been reported in prostate cancer cells which contribute to the development of the tumour environment. The specific tumour receptor mechanism of the death ligand TRAIL (tumour necrosis factor related apoptosis inducing ligand) has attracted remarkable therapeutic interest. However, many cancer cells are resistant to TRAIL monotherapy. A novel microtubule-targeting agent, PBOX-15 is known to exhibit anti-tumour activity in cancer cell lines including those with multi-drug resistance. Previous studies demonstrated that PBOX-15 is capable in sensitising cancer cells to TRAIL-mediated cell death by upregulation of death receptors and downregulation of related oncogenes. This study examined the effect of TRAIL, PBOX-15 and the combination on the target genes in prostate cancer cells. Methods RNA was extracted from treated LNCaP cells. cDNA was synthesized, and gene specific primers were subsequently used for amplification in a polymerase chain reaction (PCR) assay. Gene expression was determined using gel electrophoresis and visualised using G:BOX. The intensity of DNA bands for each sample was analysed through gel densitometry. Results c-Myc and BIRC5 expression was detected in the LNCaP cell line following a 24-hour treatment time with each treatment. TRAIL increased expression of c-Myc and BIRC5. In contrast, c-Myc expression was downregulated by PBOX-15, and PBOX-15 in combination with TRAIL showed further decreased of both c-Myc and BIRC5 expression in the LNCaP cell line. Conclusions The presence of c-Myc and BIRC5 in LNCaP cell suggested the potential as therapeutic targets in metastatic prostate cancer. PBOX-15 presented an ability to sensitise cells to the effects of TRAIL, thus provide insight in potential application of the combination for metastatic prostate cancer.